Resolution of Holliday junctions by eukaryotic DNA topoisomerase I. - Sekiguchi, J (1996)
The Holliday junction, a key intermediate in both homologous and site-specific recombination, is generated by the reciprocal exchange of single strands between two DNA duplexes. Resolution of the junctions can occur in two directions with respect to flanking markers, either restoring the parental DNA configuration or generating a genetic crossover. Recombination can be regulated, in principle, by factors that influence the directionality of the resolution step. We demonstrate that the vaccinia virus DNA topoisomerase, a eukaryotic type I enzyme, catalyzes resolution of synthetic Holliday junctions in vitro. The mechanism entails concerted transesterifications at two recognition sites, 5'-CCCTT decreases, that are opposed within a partially mobile four-way junction. Cruciforms are resolved unidirectionally and with high efficiency into two linear duplexes. These findings suggest a model whereby type I topoisomerases may either promote or suppress genetic recombination in vivo.